Auroral oval reconstruction for historical geomagnetic storms in the 18th and 19th century. Issue 3 (28th February 2023) - Wagner, D.; Neuhäuser, R.; Arlt, R.
Abstract: The investigation of extreme space weather events can yield important information about the solar activity. Here, we present the reconstruction of the auroral oval position and size based on Bayesian inference for nine historical geomagnetic storms between 1716 and 1882, including the Carrington event in 1859, by using ground‐based observations, which enables us to derive the Kp index for historical events for the first time. The results for the latter show a very high level of geomagnetic disturbance (8.2 ≤ $$ \le $$ Kp ≤ $$ \le $$ 8.7, −929 nT ≥ $$ \ge $$ Dst ≥ $$ \ge $$ −1327 nT). Furthermore, we were able to derive the position of the pole in corrected geomagnetic coordinates, where especially the longitude is in good agreement with the position derived from the gufm1 model (Jackson et al., 2000). For the eight other historical storms, the Kp and Dst indices have been calculated here for the first time. In all cases, a very high Kp index was derived. The only exception is the geomagnetic storm from March 1716, which is, with a Kp index of Kp = 7.2 ± 0.4 $$ Kp=7.2± 0.4 $$, comparable with the St. Patrick's Day storm in 2015.